2006
DOI: 10.1007/s00213-006-0582-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Chronic fluoxetine increases cytosolic phospholipase A2 activity and arachidonic acid turnover in brain phospholipids of the unanesthetized rat

Abstract: The results support the hypothesis that fluoxetine increases the cPLA(2)-mediated turnover of AA within brain phospholipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 94 publications
7
25
0
Order By: Relevance
“…The baseline concentrations of plasma unesterified fatty acids, brain esterified fatty acids, brain acyl-CoA species, and arachidonic acid kinetics in controls are similar to previous reports Lee et al 2005Lee et al , 2007. In conclusion, chronic administration of lamotrigine does not alter the turnover of arachidonic acid in brain phospholipids of the unanesthetized rat.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The baseline concentrations of plasma unesterified fatty acids, brain esterified fatty acids, brain acyl-CoA species, and arachidonic acid kinetics in controls are similar to previous reports Lee et al 2005Lee et al , 2007. In conclusion, chronic administration of lamotrigine does not alter the turnover of arachidonic acid in brain phospholipids of the unanesthetized rat.…”
Section: Discussionsupporting
confidence: 87%
“…As in our previous reports Lee et al 2005Lee et al , 2007, HPLC separation of fatty acid methylester derivatives from pooled plasma total lipid extracts confirmed that 98% of total plasma lipid radioactivity represented labeled arachidonic acid after 5 min of infusion of [1− 14 C]arachidonic acid in both the lamotrigine-treated and the control rats. HPLC separation of fatty acid methyl ester derivatives from pooled brain total lipids extracts also showed that 96% of total brain radioactivity was in the form of [1− 14 C]arachidonic acid in both the lamotriginetreated and the control rats.…”
Section: Plasma and Brain Fatty Acidssupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, classical antidepressants do not appear to add to efficacy of treatment [36], and frequently switch the depressive state to mania when administered alone to bipolar patients. While the switching tendency is not understood, studies in rats chronically administered the antidepressant fluoxetine, a selective serotonin reuptake inhibitor, indicate that this antidepressant upregulates markers of the brain arachidonic acid cascade: arachidonic acid turnover in brain phospholipids and brain activity, protein and mRNA levels of cPLA 2 [33,37]. Thus, the ability of lamotrigine to downregulate COX-2 rather than upregulate arachidonic acid cascade markers as does fluoxetine, may explain why lamotrigine does not promote switching when given to depressed bipolar patients, whereas fluoxetine does.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with lithium, valproic acid and carbamazepine, chronic fluoxetine increased the turnover of arachidonic acid in rat brain phospholipids (Figure 2). The increase in arachidonic acid turnover was also associated with increased cPLA 2 activity, protein and mRNA expression [79,80]. Unlike chronic lithium and carbamazepine, fluoxetine did not target AP-2-binding activity, but did increase protein levels of nuclear AUF-1 [AU-rich element/poly(U)-binding/degradation factor-1], possibly increasing the half-life of cPLA 2 mRNA.…”
Section: Antidepressants and The Arachidonic Acid Cascadementioning
confidence: 96%